The First Information Day: Innovation Ecosystems of Digital Cultural Assets - Paneva-Marinova, Desislava; Pavlov, Radoslav; L. Stanchev, Peter (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2017)
The first information day on innovation ecosystems of digital cultural assets will present current results of the research project Concepts and Models for Innovation Ecosystems of Digital Cultural Assets . The project aims at the search for and creation of new scientific knowledge and the achievement of fundamental results in the areas of big data, massive data mining, data management, data processing, data analytics, data visualization, etc. in the digital cultural heritage domain.